A bending deflection measuring method of inner/outer cylindrical surface parts. (1st December 2020) - Pei, Yong-Chen; Yuan, Yi; Li, Hao; Wang, Cong-Hui
Graphical abstract: Highlights: A measuring method is proposed for bending deflection of cylindrical surface parts. Peak-valley enveloping method and its algorithm are given for measuring method. Numerical simulation, algorithm accuracy and reliability are studied and verified. Results of the method specialized rig are verified by commercial testing equipment. Design method of operation parameters used by measuring algorithm is provided. Abstract: Inner/outer cylindrical surface parts are often applied into all kinds of machines. The bending deformation of these parts will affect the working performance and service life of the machine. A non-contact measuring method only using a displacement sensor and a guide rail for bending deflection is proposed in this paper. A peak-valley enveloping algorithm derived through rigorous mathematical molding and analysis can be utilized to obtain the eccentricity, direction and the corresponding cross-section position, and then the axis deflection curve can be determined. The error analysis of numerical simulation results shows that the method proposed in this paper can feature a high accuracy by setting appropriate operation parameters. Then, a specialized experiment is carried out to prove the correctness and reliability of the measuring method proposed by comparing with commercial instrument results. Finally, a parameter design method is provided to match the algorithm calculation time and measuring accuracy.